PENGARUH STRUKTUR MODAL, KUALITAS AUDIT, KINERJA KEUANGAN, AUDIT DELAY TERHADAP NILAI PERUSAHAAN - Shufi Muhammad Mushab Mujaddidi; Dirvi Surya Abbas; Hesty Ervianni Zulaecha (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2022)
The Main Purpose of This Research Is To Know The Effect Of Capital Structure, Audit Quality, Financial Performance, And Audit Delay On Company Value In Industrial Sub-Sector Manufacturing Companies Listed On The Indonesia Stock Exchange For The 2015-2021 Period. Samples Obtained by Purposive Sampling Method and Based on Criteria Selected 6 Companies As Samples of This Research. The results of this study simultaneously are that capital structure, audit quality, financial performance, audit delays have an effect on firm value.